Comprehensive tutorial on the pulsed laser deposition technique and developments in the fabrication of low dimensional systems and nanostructures - Masood, Khalid Bin; Kumar, Pushpendra; Malik, Mushtaq Ahmad; Singh, Jai (Emergent Materials, 2021)
Pulsed laser deposition (PLD) is a simple and extremely versatile technique to grow thin films and nanomaterials of a wide variety of materials. PLD allows the deposition of profoundly different materials, including high-temperature superconductors, oxides, nitrides, carbides, semiconductors, metals, and even polymers or fullerenes with high deposition rates. Growing thin films using PLD is now being used around the world for prototyping thin films of many inorganic materials and even in device fabrication protocols. This article covers the detailed development, versatility, and reliability of the ultraviolet (UV) excimer laser. It is envisioned that this review article is of interest for both the materials and chemical scientists engaged in more fundamental aspects of pulsed laser ablation and deposition. The present article highlights the historical developments of PLD technique, complete mechanism of thin film fabrication, optimization of the quality of thin films and the fabrication of thin films of the materials like ZnO, Graphene, MoS2, and WS2 which are being explored for various potential applications.